PELAKSANAAN PEMBELAJARAN DARING PRODI PENDIDIKAN GEOGRAFI UNP DI MASA PANDEMI COVID-19 - ramadhan fahrul (JURNAL BUANA, 2021)
This study aims to determine the implementation of online learning in geography learning and to find out the obstacles to implementing online learning in geography learning. This type of research uses qualitative methods. The informants in this study used purposive sampling, namely 19 geography education students, 12 geography education study program lecturers. Data collection techniques using interviews, google from, and documentation. Data analysis techniques used data reduction, data presentation, and inference. The validity of the data used extended participation and observation persistence. The results of this research state that: 1) the hardware that is often used is in the form of laptops, computers, notebooks and smartphones, with available wifi network connections and using data, using zoom metting applications, google mett, E-learning and WhatApp, and providing reading material in the form of books, articles / journals. 2) his subordinates in using laptop and smartphone hardware often experience errors and also full internal storage, for internet networks often experience interference, E-learning applications often experience errors, and in providing reading material most students have difficulty getting books or learning resources because in the area where they live there is a lack of learning facilities.